EXPLORING THE IMPACT OF ISLAMIC BANKING ON ECONOMIC GROWTH: A REVIEW STUDY OF CONVENTIONAL AND ISLAMIC BANKING SYSTEMS - Erwan Iskandar (PT. Berkah Digital Teknologi, 2023)
Purpose of the study — This study aims to fill this gap by conducting a comparative analysis of the impact of Islamic and conventional banking systems on economic growth.Research method— Literature review by examining the key principles and practices of Islamic banking, as well as the relevant theories and empirical evidence.Result— this research will shed light on the unique features of Islamic banking that contribute to its potential impact on economic growth. The results of this study will provide valuable insights for policymakers, economists, and practitioners, as well as for scholars who are interested in the field of Islamic finance.Conclusion— The study aimed to analyze the impact of Islamic and conventional banking systems on economic growth through a literature review. The results showed that Islamic banking has a positive impact on economic growth, especially in GCC countries and several East Asian countries. The relationship between GDP per capita and economic growth is weaker if Islamic banking is taken into account, and the relationship varies based on the legal origins of the country. The study found that the only significant factor of Islamic banking performance that influences economic growth is profit. This study provides valuable insights for policymakers, economists, and practitioners in the field of Islamic finance.